ARROBO, Augmented Reality-Based Mobile Application for Supporting Innovative Learning in Robotics - Yusuf, Abdur Rachman; Efendi, Agus; Yuana, Rosihan Ari (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The results of the study show that the use of technology in the classroom has a positive impact on students learning and behavior. The use of technology in education also makes students more independent in learning. One form of technology is augmented reality. Augmented reality is a technology to produce and combine virtual objects into the real world. In learning robotics, there are several problems, namely limited costs and the limited number of tools. Obstacles to learning robotics in addition to the cost and number of tools, namely the limited time and condition of the class that must be arranged so that it is not chaotic. In this study, will be discussed on the development of an augmented reality mobile application named ARROBO. The purpose of making ARROBO is to overcome the problem of limited costs and the limited number of tools. In addition to discussions about development, this paper will also be presented on the results of the feasibility test of the learning media. Based on the results of the feasibility test using ISO 25010, the results obtained in the functional suitability aspect obtained a score of 100%, the portability aspect obtained a score of 100%, media expert ratings obtained a score of 90%, and usability aspects obtained a score of 84%. In addition, the assessment of material experts obtained 100% results on aspects of material accuracy. Based on these results it can be concluded that the ARROBO application belongs to the "Very Worthy" category to use.